Crustal-to-mantle shifting in SiO2-rich upper crustal magmas through zircon and bulk rock compositions in the Famatinian arc - Escribano, Facundo Agustín (2025)
The Famatinian arc developed an outboard continental magmatic belt on the western margin of the Early Paleozoic Gondwana. Between 27° and 28° south latitude of the Argentinian Andean foreland, the Chaschuil section preserves an exceptional window into the upper crustal magmatism. New zircon U-Pb dating, trace elements and O-Hf isotope analyses, coupled with bulk rock chemistry and field relationships unravel multi-stage igneous processes during the development of arc volcanism. Our results shed light on two primary magmatic stages with distinct chemical trends, synchronized with regional-scale magmatic tempos. The Narvaez Batholith represents the initial stage of the magmatic column construction during 490–478 Ma, forming strongly peraluminous granites with high δ18OZircon values (~7.5 to 9.6 ‰) and negative εHf(t) signatures (~-6.3 and -0.6). This early phase was followed by a high magma flux event at 470 ± 3 Ma, which led to the development of the Las Planchadas Plutonic-Volcanic Complex. This complex comprises a weakly peraluminous granite-rhyolite sequence, distinguished by a shift towards lower δ18OZircon (4.0 to 5.8 ‰) and positive εHf(t) values (0.0 to +7.6). The εHf-δ18O ratios in zircon define mixing and AFC arrays indicating an early widespread reworking of pre-existing thick turbidite sequences by advected mantle-derived melts. The following high magma flux event involved the growth of magma chambers by incremental melt extraction from a virtually uncontaminated arc mantle source undergoing advanced differentiation upon eruption. The progressive development of magma chambers and an accumulation of plutons shielded (or exhausted) the metasediments, preventing further influx of crustal partial melts into the magmatic system on their pathway through the lithosphere. This scenario elucidates the time-dependent roles of crustal assimilation, crystal fractionation, and mixing of subduction-related magmas during protracted arc-building processes that eventually lead to eruptions. Our findings provide deep insights into the puzzling compositional variations between bulk rock and zircon data in magmatic plumbing systems and their key relationship with the pre-existing (meta)sedimentary or igneous rocks.